Voglio essere presente come vita : Liana Millu et sa voix singulière de Birkenau - Teklik, Joanna (Studia Romanica Posnaniensia, 2018)
Contemporary research on remembrance yields more and more women’s concentration camp testimonies and evidence of their unique character. The names quoted in these materials include Liana Millu (1914-2005), an Italian women of Jewish descent, an Auschwitz-Birkenau and Ravensbrück prisoner. Her work proves that the experience of trauma, though unimaginable, is utterable. Millu resorts to literary fiction to outline life stories of Birkenau women, their typical problems, ways of dealing with tham, as well as the survival strategies thay employed. Liana Millu’s testimony is an unusual attempt to show how women experienced the trauma of the camp.